Perbandingan Implementasi Produk Gadai Emas Pada Pegadaian Syariah Dan Bank Syariah: Studi Kualitatif Fenomenologis - Merry Meilany (EL-EMIR Institute, 2025)
This study examines the implementation of gold pawn products at Islamic Pawnshops (Pegadaian Syariah) and Islamic Banks in Indonesia using a qualitative phenomenological approach. Gold pawn products are one of the short-term financing instruments widely favored by the public because they are backed by gold as an underlying asset with relatively stable value. Differences in business models, cost structures, types of contracts applied, operational mechanisms, and levels of compliance with Sharia principles between Islamic Pawnshops and Islamic Banks result in varying customer experiences. Research data were collected through in-depth interviews with customers, employees, and Sharia economics practitioners, and were supported by a review of relevant national and international journal literature. The findings indicate that, in terms of cost, gold pawn products offered by Islamic Banks are relatively cheaper than those provided by Islamic Pawnshops. However, in terms of process and service, Islamic Pawnshops have advantages in simpler administrative procedures and faster disbursement times. These differences influence customer perceptions of service convenience, cost transparency, and Sharia compliance. This study provides important implications for improving service quality, refining internal regulations, and strengthening the application of Sharia principles in the development of gold pawn products within Islamic financial institutions.